Business Model Canvas : Miracle Secret / Mohd Pawiro Santono Othman - Othman, Mohd Pawiro Santono (2020)
For Miracle Secret that we had been introduced, this is one of the cosmetic supplement that have same function (fat burning, skin whitening, weight loss) with the others that already exist in the current market. However, it comes with new features in term of ingredients. We used natural and organic compound such as Fructus Garcinia Cambogia (Asam Gelugor), Green Tea Leaves and Labis Pumila (Kacip Fatimah). All this ingredients scientifically prove that has benefit for our body when we consume it. This value proposition of Miracle Secret has meet customers demand which is demand for a safe cosmetic product but at the same time it is efficient. Moreover, Miracle Secret is come with three different flavour which are chocolate, strawberry and vanilla. So, customers that want to try it can choose which flavour they like and just chew it like a candy when consume this Miracle Secret. Last but not least, we are pretty sure that Miracle Secret has high potential to be widely sold since it is has its own unique compare to others cosmetic supplement